The Heinemann Illustrated Dictionary OF Health & Social Care - Nolan, Yvonne (Harlow : Heinemann, 2009)
Suitable for those studying and working in health and social care, this book features over 1,500 definitions and explanations, covering requirements of National Occupational Standards for learners and teachers/tutors in schools, colleges and the workplace.
Keywords: Social service -- Great Britain -- Dictionaries; Medical care -- Great Britain -- Dictionaries; Society